How can we avoid eating ourselves out of water? - Hess, Tim M. (Nature, 2021)
Agriculture is the main contributor to global water scarcity but not all diets contribute equally. Modifying what, and how much, we eat could reduce the impact of our diets on global water resources.
Keywords: Hydrology; Health humanities